Enhancing Digital Marketing Capacity in Local Livestock Businesses: The Banten Farm Case - Oktini, Dede R.; Rabiatul Adawiyah; Nurdin; Fitriyanti, Andina Adma; Arlinda, Riza; Fujhita, Bella (ETHOS: Jurnal Penelitian dan Pengabdian kepada Masyarakat, 2026)
The rapid growth of digital technology has transformed marketing practices across various business sectors, including livestock enterprises. However, many small-scale livestock businesses still face challenges in utilizing digital marketing tools effectively due to limited digital literacy and a lack of technical assistance. This community service program aimed to enhance the digital marketing capacity of Banten Farm through training and mentoring activities. The program was conducted from July to August 2025 and involved 15 participants consisting of farm staff, business owners, and students. The implementation consisted of four stages, namely needs assessment, training, hands-on practice, and evaluation. The evaluation results showed that all participants successfully created digital business accounts and developed promotional content using Instagram and WhatsApp Business. Participants also demonstrated an improved understanding of digital marketing concepts, online customer engagement, and content creation strategies. The program indicates that practical and participatory training can contribute to improving the digital marketing capabilities of local livestock enterprises. Continuous mentoring is recommended to ensure the sustainability of digital transformation initiatives in rural agribusiness sector.